Otimização da extração de compostos fenólicos das folhas de Tabernaemontana catharinensis e avaliação dos marcadores de estresse oxidativo em ratos diabéticos - Sari, Rafael (2018)
Tabernaemontana catharinensis (T. catharinensis) is a medicinal plant of the Brazilian flora which stands out for its high antioxidant potential. The plant is popularly known as blancule and its leaves, barks and roots are used to combat diseases related to oxidative stress such as gastroenteritis, syphilis and leprosy. The objective of the present study was to optimize the extraction of phenolic compounds from T. catharinensis using a factorial design of 23 solvent variables (Ethanol and Ethyl Acetate), time (30 and 60 minutes) and temperature (350 and 650 0C) to later analyze the activities antioxidants in vitro and the effect under oxidative stress in the animal experimental model of diabetes. In the evaluation of the in vitro antioxidant capacity the sequestering power of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis- (3-ethyl-benzothiazoline-6-sulfonic acid) radicals was determined ABTS), antioxidant iron reduction power (FRAP), and oxidation of the β-carotene / linoleic acid system. In the animal experimental model of diabetes, lipid peroxidation (TBARS), catalase (CAT), glutathione s-transferase (GST) and superoxide dismutase (SOD) were determined in liver, kidney, spleen and total brain tissues of Wistar rats. The characterization and quantification of the profile of phenolic compounds were determined by high performance liquid chromatography (HPLC) and the data set was analyzed by response surface methodology and principal component analysis (PCA). Using extract A8 which was the best extraction condition for the determinations, in vitro and ex vivo, was used. The results demonstrate that ethanol solvent was more efficient in extracting the phenolic compounds of T. catharinensis incorporated at higher temperature (65 0C) and time (60 min). The solvent ethyl acetate mostly extracted the phenolic compound pinocembrina which has characteristic of extraction in less polarity using the temperature of 65 ° C and the time of 60 min. In vitro results demonstrated that the A8 extract has a satisfactory antioxidant action with 23.34 mg EAG / g-1 for CFT, 34.26 μmol Trolox for DPPH, 24.13 μmol Fe2+ for FRAP, 12.57 10 μmol Trolox for ABTS and 78.85% AA for β-carotene / linoleic acid. The results of oxidative stress markers in diabetic rats demonstrated that the A8 extract from the leaves of T. catharinensis administered via gavage in diabetic rats decreased GST activity in the liver and SOD in the whole brain. It is concluded that the methodology developed for the extraction of the phenolic compounds from the leaves of T. catharinensis is promising and has a satisfactory in vitro antioxidant potential. However, the use of the plant extract A8 to combat oxidative stress in the experimental animal model of diabetes did not demonstrate be efficient and requires additional studies for application as an antioxidant in biological activities.